Experiences, activities, and personal characteristics as predictors of engagement in STEM‐focused summer programs. Issue 8 (8th May 2020) - Schmidt, Jennifer A.; Beymer, Patrick N.; Rosenberg, Joshua M.; Naftzger, Neil N.; Shumow, Lee
Abstract: Out‐of‐school‐time programs for youth that are focused on STEM content are often seen as affording opportunities to increase youth engagement, interest, and knowledge in STEM domains, yet we know relatively little about how youth actually experience such programs. In this article, we explore how experiences and activities employed in the delivery of summer STEM programs are associated with youth engagement during programming, and whether youth characteristics moderate these relationships. Data were collected from 203 youth (ages 10–16) in nine summer programs using multiple methods including video, experience sampling, and surveys. Through the use of cross‐classified, multi‐level models, we found that youth reported higher engagement in program activities they perceived to be more challenging and relevant, and in activities, they perceived to have more affordances for learning or developing skills. Gender moderated these relationships such that the positive relationships observed among males were muted or nonexistent for girls. We further identify that program activities are differently associated with fostering challenge, relevance, and learning. Findings have implications for out‐of‐school STEM programming for youth.